Morphological characteristics of the piriform cortex in rats with various neurocognitive disorders after traumatic brain injury - Mizyakina , K.V. (Морфологія / Morphologia / Morfologìâ, 2024)
Background. In solving numerous issues related to the treatment and rehabilitation of patients with traumatic brain injury, it is of particular interest to study the pathomorphological mechanisms that determine the nature of the formation and dynamics of neurocognitive disorders at various times after the injury. The study aims to determine the tissue and cellular posttraumatic changes in the structure of the piriform cortex of rats with various neurocognitive disorders at different times after severe traumatic brain injury. Methods. A "shock acceleration model" was used to reproduce severe traumatic brain injury in rats. According to the results of neurological tests, the rats were divided into three groups: 1) the first – animals after trauma with neurocognitive disorders and memory disorders; 1) the second – animals after trauma with neurocognitive disorders without memory disorders; 3) comparison group – animals after trauma without neurocognitive disorders. A histological, morphometric and immunohistochemical study of the piriform cortex was carried out using the markers β-tubulin, Synaptophysin, GAP43, NCAM1, N-cadherin, GFAP. Results and conclusion. Neurocognitive disorders with memory impairment in the long-term after TBI are accompanied by a deepening of the degeneration of neurocytes of the piriform cortex and the chronicity of neuroinflammation with the activation of the mechanisms of neuronal apoptosis and gliocyte autophagy. The progression of neurodegeneration is accompanied by the activation of microglia and leads to the disintegration and migration of macrogliocytes with the formation of an irreversible mosaic astrocytic deficiency and the formation of glial layers in the form of clutches around hemocapillaries. The preservation of memory function in animals with neurocognitive disorders is associated with the limitation of secondary death of neurocytes and the stabilization of the adhesive properties of astroglia of the piriform cortex, which prevents the formation of astrocytic clutches around newly formed hemocapillaries while maintaining the integrity of the blood-brain barrier. In animals without neurocognitive disorders in the long-term post-traumatic period, compensatory mechanisms in the piriform cortex are implemented through effective neovasculogenesis, limitation of perivascular astrocyte hyperplasia, and neuroinflammation, which prevents neurocyte death and leads to activation of synaptic remodeling.